Artikel Membedah Retorika-Komunikasi Politik dan Implikasinya Pada Pemilu di Tahun 2024 - Pontoan, Karen Alfa; Loho, Ambrosius Markus (Indo-MathEdu Intellectuals Journal, 2023)
Rhetoric or political communication is important for people who are preparing for a political contestation. As we know, rhetoric really needs to be explored in detail, so that the process of gaining votes in the context of elections can be significant. Therefore, the choice of rhetorical models is always needed by contestants. This article aims to dissect the rhetorical models that exist and have become the choice of contestants in an election. The method the author uses is to start from a general description of the rhetorical model, then from there it will be dissected the meaning of this rhetorical model, if it can be the choice of the contestants. In line with that, the result obtained from dissecting these rhetorical models is a combination of the rhetorical models of Aristotle, Lasswell and Interactionalism. From the combination of these models, it will clarify to the contestant the rhetoric he needs to use to achieve his goal of electability or significance in terms of his electability